Administrative Sanctions For Abuse Of Authority In The Field Of Environmental Licensing - Zahra Malinda Putri (Fakultas Hukum, Universitas Islam Bandung, 2022)
Every government action in implementing government administration must be based on the applicable laws and regulations. One of them is in making a state administrative decision, namely Permit. However, often the issuance permits issued by government agencies or officials are contrary to laws and regulations, such as environmental permits. This is a form of abuse of authority in the form of exceeding the authority based on Article 18 paragraph (1) of Law Number 30 of 2014 concerning Government Administration. This study aims to determine the administration of administrative sanctions against acts of abuse of authority in the field of environmental licensing based on positive law in Indonesia. This research uses a normative juridical approach with a qualitative normative analysis method. The results of the study conclude that administrative sanctions against government agencies or officials in committing acts of abuse of authority in the field of environmental licensing are not regulated in Law Number 32 of 2009 concerning Environmental Protection and Management but are regulated in the Government Administration Act, namely receiving administrative sanctions heavy.